Study of automatic generation control in two area power system with DFIG-based wind energy conversion - Kail, Soumia; Bekri, Abdelkader; Hazzab, Abdeldjebar (Institute of Advanced Engineering and Science, 2019)
The main objective of Automatic Generation Control (AGC) is to keep the frequency within specified limits through primary and secondary control. In this study, a model of two area thermal non-reheat power system with integration of Doubly Fed Induction Generator (DFIG) based Wind Energy Conversion (WEC) into both areas is presented. A Proportional Integral Derivative (PID) controller and a Fuzzy Logic Controller (FLC) have been applied and compared. The Proposed controllers are used to improve the dynamic response as well as to reduce or eliminate the steady-state error in Area Control Error (ACE). FLC has been offered better and faster performance over the PID controller. The results obtained prove the impact of DFIG-based WEC on AGC and confirm the participation of the DFIG in the frequency system.